Recurrent Villous Adenoma with High-Grade Dysplasia Arising in a Urethral Diverticulum - Alireza Zarineh; Elena Bulakhtina; Peter R. Olson; Jan F. Silverman (Case Reports in Medicine)
Villous adenomas of the urinary tract are an uncommon, well-recognized entity, described in different locations. However, the occurrence of this lesion in the female urethral diverticulum is very unusual. We present the first case of a recurrent villous adenoma with high-grade dysplasia unassociated with adenocarcinoma, arising from a urethral diverticulum. A 75-year-old African-American female presented with urethral prolapse complaining of mild voiding difficulty, stress incontinence, and mild spotting of blood. Histological examination revealed a papillary lesion with finger-like processes lined by pseudostratified columnar epithelium with abundant goblet cells. There were focal areas with stratification to the luminal surface and loss of nuclear polarity and atypical mitoses, interpreted as villous adenoma with high-grade dysplasia. The lesion recurred at one year without evidence of malignant transformation. We also present a brief literature review of urothelial villous adenomas.